Master your inner game and maximize your performance - Årsland, Benedicte ([B. Årsland], 2014)
This essay is about the mental aspects of being a performer. To be a peak performer, you need technical and musical skills. However, you also need a strong and trained mind. You need to know how to focus your mind to the maximum. I will write about the "inner game"; how our mind is working during preperation time and during pressure. The goal is to be able to control your thoughts, so that they help you, instead of destroy you. I want to give you some ideas of how to understand the mental aspects of a performance. Your performance depends on mental understanding, preparation and training, in addition to intrumental practicing. This knowledge can support you to become a more confident player, and to make performing more enjoyable for yourself and others. ?
Keywords: mielikuvaharjoittelu; fi=jouset|sv=stråkar|en=Strings|